2015
DOI: 10.1038/ijo.2015.181
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of leptin on adiponectin expression with weight gain versus obesity

Abstract: Background/ObjectiveAdiponectin exerts beneficial effects by reducing inflammation, and improving lipid metabolism and insulin-sensitivity. Although adiponectin is lower in obese individuals, whether weight gain reduces adiponectin expression in humans is controversial. We sought to investigate the role of weight gain, and consequent changes in leptin, on altering adiponectin expression in humans.Methods/ResultsForty four normal-weight healthy subjects were recruited (mean age 29 years; 14 women) and randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 58 publications
4
40
1
Order By: Relevance
“…However, some studies have reported no change in adiponectin levels despite improvements in glucoregulation [2325]. Furthermore, in healthy weight subjects, adiponectin decreases with weight loss [26] and increases with weight gain [27], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, some studies have reported no change in adiponectin levels despite improvements in glucoregulation [2325]. Furthermore, in healthy weight subjects, adiponectin decreases with weight loss [26] and increases with weight gain [27], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…While Ad and leptin were described as two independent factors which are dysregulated in MetS [48], recent studies found that leptin could induce Ad expression in differentiated human white preadipocytes [49], in ob/ob [50, 51] and in LDLR -/- mice [51]. Singh et al also suggested that leptin resistance may contribute to the reduced Ad expression in obese patients [49]. However, further in vivo and clinical investigations are necessary to confirm any causal relationship between leptin level and Ad expression.…”
Section: Discussionmentioning
confidence: 99%
“…HMW adiponectin is the major insulin-sensitizing isoform in humans [28] . Previous studies have shown that total adiponectin levels were increased after short term high-fat overfeeding for 3-7 days or 8 weeks [20,25,30] . No change in HMW adiponectin was observed in this study after 3 days.…”
Section: Discussionmentioning
confidence: 99%